If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12n-6(1-12n)=3(12n-2)
We move all terms to the left:
12n-6(1-12n)-(3(12n-2))=0
We add all the numbers together, and all the variables
12n-6(-12n+1)-(3(12n-2))=0
We multiply parentheses
12n+72n-(3(12n-2))-6=0
We calculate terms in parentheses: -(3(12n-2)), so:We add all the numbers together, and all the variables
3(12n-2)
We multiply parentheses
36n-6
Back to the equation:
-(36n-6)
84n-(36n-6)-6=0
We get rid of parentheses
84n-36n+6-6=0
We add all the numbers together, and all the variables
48n=0
n=0/48
n=0
| 6x+33+3x+30=180 | | 5.3(x-5)=2.94+3.7 | | c=51(18)+4.4 | | 3a-5=37 | | 7x+21=5x+49 | | 5/12=3.5/x | | 6-2x=6x10x+16 | | 2x+21=5x+49 | | (6+8)2=-9x5 | | 12/5=x/3.5 | | 1/29(x)=6 | | 2(3x+1)+3(x-7)=265 | | 3x-9+x+x=180 | | -3x+22=-20 | | -32=2d | | 13=-7x-29 | | -5x=2x-2 | | 2x-3(x-3)=8 | | (7y+18)+(2y+17)=180 | | -7x-2.3=7x-7.0 | | 12/5=3.5/x | | (3x8)x4=3x({}) | | 4x+8+3x+5=90 | | -3(x+4)=8x-34 | | 5x-7+24=90 | | 10(10+9m)–7m=11(4m+2) | | 49=13−4x | | -1/2x+2/3=1/4 | | -11=8x-13 | | -7x+2+5x=2x+7 | | 50=7p-15 | | 5/v=2/5 |